Epigenetic mechanisms in the regulation of lymphocyte differentiation - Schmolka, Nina (2020)
Epigenetics refers to heritable phenotype changes that do not involve alterations in the DNA sequence. While DNA methylation and histone modifications represent the classical epigenetic mechanisms, RNA-based interference can also be integrated into the epigenetic machinery. In particular, microRNAs play important roles in regulating gene expression at the posttranscriptional level. Thus, from the nucleus to the cytoplasm, various “epigenetic” mechanisms can control cell fate decisions and differentiation. This has been extensively documented in lymphocyte biology, from a commitment to the B- and T-cell lineages to the differentiation of multiple effector lymphocyte subsets. Here we review the accumulated knowledge that fundaments our understanding of how classical epigenetics and RNA-based regulatory mechanisms impact B- and T-cell differentiation.